2022
DOI: 10.3346/jkms.2022.37.e60
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Incidence of Intussusception and Infectious Diseases After the COVID-19 Pandemic in Korea

Abstract: Background Intussusception refers to the invagination of a part of the intestine into itself. The exact cause for this condition is unknown in most cases. The active implementation of coronavirus disease 2019 (COVID-19) infection control guidelines has reduced the spread of COVID-19 and the incidence of other infectious diseases in children. The current study aimed to identify changes in pediatric intussusception and infectious diseases after the implementation of infection control guidelines and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…During the COVID-19 (coronavirus disease 2019) pandemic in Korea, however, pediatricians saw a magnificent decrease in the incidence of respiratory viral infections and several infection-related diseases. 2 3 In addition, the observation, i.e., the decrease of pediatric respiratory infections, was supported in the nationwide infectious disease surveillance. 4…”
mentioning
confidence: 85%
“…During the COVID-19 (coronavirus disease 2019) pandemic in Korea, however, pediatricians saw a magnificent decrease in the incidence of respiratory viral infections and several infection-related diseases. 2 3 In addition, the observation, i.e., the decrease of pediatric respiratory infections, was supported in the nationwide infectious disease surveillance. 4…”
mentioning
confidence: 85%
“…Enteric and non-enteric types of adenovirus infection had significant associations in multiple studies, being reported in approximately 30-40% of cases [16][17][18] . Yoo et al recently investigated the incidence of monthly visits for intussusception from seven hospitals in Korea in 2017-2020 19) . Interestingly, the incidence of monthly visits has substantially reduced (9.0 to 3.5) after the active implementation of the coronavirus 2019 infection control guidelines initiated in Korea.…”
Section: Epidemiology and Pathogenesismentioning
confidence: 99%
“…These measures have led to unprecedented changes in behavioral patterns, as well as the occurrence of other infectious diseases [ 5 ]. For example, previous studies have shown a significant decline in the incidence of upper and lower respiratory tract infections such as seasonal influenza, and some non-infectious diseases in pediatric populations [ 5 , 6 , 7 , 8 , 9 , 10 ]. However, there are a lack of national-level data on yearly or seasonal changes in the incidence rates of gastrointestinal (GI) diseases, which are commonly encountered in clinical settings.…”
Section: Introductionmentioning
confidence: 99%
“…These lifestyle changes have also drastically reduced the incidence of other infectious diseases [ 5 ], such as GI viral infections that are transmitted through the fecal-to-oral route or direct contact between people [ 14 ]. Hence, the COVID-19 pandemic may have had a major influence on the occurrence and management of other GI diseases [ 6 ]. Since GI symptoms are also observed in patients with COVID-19 and have been associated with severe COVID-19 disease [ 15 ], healthcare providers should promptly differentiate between COVID-19 and non-COVID-19 GI diseases, keeping in mind the prevalence of GI diseases.…”
Section: Introductionmentioning
confidence: 99%